A combination of deep eutectic solvent and ethanol pretreatment for synergistic delignification and enhanced enzymatic hydrolysis for biorefinary process. (April 2022) - Yao, Lan; Cui, Pingping; Chen, Xiong; Yoo, Chang Geun; Liu, Qianting; Meng, Xianzhi; Xiong, Long; Ragauskas, Arthur J.; Yang, Haitao
Highlights: Synergistic effects of DES with ethanol were investigated. DES-E pretreatment results a better glucose yield. Ethanol in pretreatment liquor protected β-O-4 from degradation and condensation. Residue lignin after DES-E pretreatment showed less adsorption ability to cellulase. DES-E pretreatment is a promising method in biorefinery. Abstract: A novel pretreatment system containing deep eutectic solvents and ethanol (DES-E) for synergistic carbohydrate conversion and delignification was reported in this study. The DES-E pretreatment resulted in an enhanced glucose yield compared to individual DES and ethanol pretreatment for the three tested biomass, including Broussonetia papyrifera, corn stover and pine. To further explore the delignification mechanism, the solubilized lignin and residual lignin from Broussonetia papyrifera was recovered and extracted, then thoroughly characterized. The highest total OH content was found in the DES-E solubilized lignin, which could be used as antioxidant. The presence of ethanol in pretreatment liquor could protect the β-O-4 substructure from breakage and reduce lignin condensation, which favors the subsequent enzymatic hydrolysis. Comparable glucose yield and delignification performance was achieved by recycled DES. DES-E pretreatment offers a promising method for lignin isolation and cellulose digestibility improvement simultaneously.